Pengaruh Harga dan Gratis Ongkir Terhadap Keputusan Pembelian Tokopedia di Tuban - Siti Rima Widya Listi; Aisyah Darti Megasari; Komarun Zaman (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the influence of price and free shipping on purchasing decisions. This is a quantitative study using primary and secondary data. The sampling technique used was non-probability sampling with purposive sampling using the Slovin formula to determine the minimum number of respondents. The results of this study indicate that price influences purchasing decisions, free shipping does not influence purchasing decisions, and both price and free shipping influence purchasing decisions.